2007
DOI: 10.1037/0278-7393.33.4.734
|View full text |Cite
|
Sign up to set email alerts
|

The cost of event-based prospective memory: Salient target events.

Abstract: Evidence has begun to accumulate showing that successful performance of event-based prospective memory (PM) comes at a cost to other ongoing activities. The current study builds on previous work by examining the cost associated with PM when the target event is salient. Target salience is among the criteria for automatic retrieval of intentions according to the multiprocess view of PM. An alternative theory, the preparatory attentional and memory processes theory, argues that PM performance, including retrieval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

36
394
6
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(437 citation statements)
references
References 40 publications
36
394
6
1
Order By: Relevance
“…The PAM theory (Smith, 2003;Smith & Bayen, 2004;Smith et al, 2007) argues that, during the interval in which the prospective memory task must be executed, "successful true [prospective memory] performance requires that preparatory attentional processes be engaged" (Smith et al, 2007, p. 742). Furthermore, the PAM theory argues that we do not have to be consciously aware of the engagement of preparatory (e.g., monitoring) processes, but nevertheless, these processes will consume attentional resources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PAM theory (Smith, 2003;Smith & Bayen, 2004;Smith et al, 2007) argues that, during the interval in which the prospective memory task must be executed, "successful true [prospective memory] performance requires that preparatory attentional processes be engaged" (Smith et al, 2007, p. 742). Furthermore, the PAM theory argues that we do not have to be consciously aware of the engagement of preparatory (e.g., monitoring) processes, but nevertheless, these processes will consume attentional resources.…”
Section: Discussionmentioning
confidence: 99%
“…1 Monitoring theories such as the preparatory attentional and memory processes (PAM) theory argue that monitoring or other preparatory processes must be engaged prior to the occurrence of a target event for an intention to be successfully retrieved (Smith, 2003;Smith & Bayen, 2004;Smith, Hunt, McVay, & McConnell, 2007). These processes are assumed to be nonautomatic and to require attentional or working memory capacity and may be conscious or unconscious (Smith et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The fixation-cross duration was varied to prevent participants from using the interstimulus interval for an attentional break (cf. Smith, Hunt, McVay, & McConnell, 2007). After participants responded to the probe stimulus, a new fixation cross was presented after a blank screen of 500 ms.…”
Section: Procedures and Materialsmentioning
confidence: 99%
“…Numerous studies have demonstrated that response times to ongoing tasks on nontarget trials are slowed when individuals need to remember to perform PM tasks, an effect referred to as the costs to ongoing tasks (for a review, see Smith, Hunt, McVay, & McConnell, 2007). Costs have been interpreted as evidence for the allocation of some form of attentional capacity to the PM task and have formed the primary dependent measure for determining the resource requirements of PM (Einstein & McDaniel, 2010;Smith, 2010).…”
mentioning
confidence: 99%